Membrane Bioreactor-Desalination Microbial Fuel Cell Hybrid System - Mukhtar, Noora Hussein Adam (2018)
A Master of Science thesis in Chemical Engineering by Noora Hussein Adam Mukhtar entitled, “Membrane Bioreactor-Desalination Microbial Fuel Cell Hybrid System”, submitted in April 2018. Thesis advisor is Dr. Sameer Al-Asheh and thesis co-advisor is Dr. Ahmed A. Aidan. Soft and hard copy available.